Mechanical and Physical Properties of Glass Wool-Rigid Polyurethane Foam Composites - Marhoon, Ismail Ibrahim; Rasheed, Aseel Kais (Nahrain University College of Engineering Journal, 2015)
This research is devoted to the preparation of foam polymer matrix composite materials by forming in place method, where the composite foam material was prepared from the rigid polyurethane foam (PU) as a matrix reinforced by glass wool insulator with weight fractions (2%, 4%, 6%, 8% and 10%) .Several mechanical and physical tests were done and these include impact, flexural, compression, hardness, density, water absorption and thermal conductivity. The result shows that the values of mechanical and physical properties in general are increased with the increase of glass wool weight fraction content. The values of flexural strength decrease with the increase of weight fraction of glass wool fiber after 8% wt.